СLINICAL EFFICIENCY OF STATINS IN RHEUMATOID ARTHRITIS: A PILOT STUDY - I. V. Shirinsky; O. I. Zheltova; N. Yu. Solovieva; V. S. Shirinsky; V. A. Kozlov (Медицинская иммунология, 2014)
Abstract. Statins are widely used to lower lipid levels and prevent cardiovascular disease. Recently described anti-inflammatory and immunomodulating properties of statins substantiate their application as a potentially novel treatment for autoimmune diseases. We evaluated efficacy and safety of simvastatin (40 mg daily) in patients with active rheumatoid arthritis (RA), as a supplement to stable doses of disease-modifying antirheumatic drugs. After 12 weeks of treatment, there was registered a significant decrease in disease activity score (by 0.89 points), improvement of life quality, and attenuation of pain levels. To confirm efficacy and safety of simvastatin in active RA, a large-scale controlled randomized study should be performed.